Pengaruh Viral Marketing, Online Consumer Review dan Live Streaming Terhadap Keputusan Pembelian Produk Skincare Skintific pada Platform TikTok - Nuraisah; Elang Ilik Martawijaya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of Viral Marketing, Online Consumer Review and Live Streaming on the Tiktok platform. This study uses a Quantitative method. The type of research data used is primary data obtained based on the distribution of questionnaires to 100 respondents. The sampling used uses non-probability with a purposive sampling technique with the criteria of consumers who have purchased skintific products in this study. The data analysis method is carried out using multiple linear regression analysis. The test results show that the variables Viral Marketing, Online Consumer Review and Live Streaming have a positive effect on the decision to purchase Skintific Skincare on the Tiktok platform.